2008
DOI: 10.3354/meps07395
|View full text |Cite
|
Sign up to set email alerts
|

Trophic interactions under stress: hypoxia enhances foraging in an estuarine food web

Abstract: Ecosystem-level effects of stressors are critical to understanding community regulation, and environmental stress models are useful in describing such effects. Hypoxia is an important stressor in aquatic ecosystems that usually decreases abundance and biomass of benthic fauna. In field surveys, predator abundance is low in hypoxic areas, and in lab experiments, predators reduce their feeding rates under hypoxic conditions, leading to the hypothesis that consumer stress models (CSMs), rather than prey stress mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 46 publications
1
39
0
Order By: Relevance
“…Such behavior probably induces a tradeoff between foraging and physiological stress that may lead to enhanced prey consumption in the short term. However, hypoxiainduced increases in short-term foraging may also lead to negative effects in the long term such as prey depletion, a less resilient prey community, and cumu lative effects of physiological stress (Wu 2002, Costantini et al 2008, Long & Seitz 2008. The higher avoidance thresholds under more severe hypoxia documented here suggest that hypoxia avoidance is context-dependent, as has been shown in other systems (Bell & Eggleston 2005, Pierson et al 2009).…”
Section: Vertical Avoidance Of Bottom Water Hypoxiasupporting
confidence: 54%
See 1 more Smart Citation
“…Such behavior probably induces a tradeoff between foraging and physiological stress that may lead to enhanced prey consumption in the short term. However, hypoxiainduced increases in short-term foraging may also lead to negative effects in the long term such as prey depletion, a less resilient prey community, and cumu lative effects of physiological stress (Wu 2002, Costantini et al 2008, Long & Seitz 2008. The higher avoidance thresholds under more severe hypoxia documented here suggest that hypoxia avoidance is context-dependent, as has been shown in other systems (Bell & Eggleston 2005, Pierson et al 2009).…”
Section: Vertical Avoidance Of Bottom Water Hypoxiasupporting
confidence: 54%
“…Supporting this possibility, sediment cores taken in 2003 indicated that infaunal prey were moderately abundant at hypoxic sites, with the highest prey densities within the upper 1 to 2 cm layer of the sediment ). Numerous studies have demonstrated that mobile organisms will tolerate shortterm exposure to low DO in order to access hypoxic habitats that harbor food resources (Rahel & Nutzman 1994, Nestlerode & Diaz 1998, Taylor et al 2007, Long & Seitz 2008, Craig et al 2010. Such behavior probably induces a tradeoff between foraging and physiological stress that may lead to enhanced prey consumption in the short term.…”
Section: Vertical Avoidance Of Bottom Water Hypoxiamentioning
confidence: 99%
“…Croaker appears to remain benthic feeders under hypoxia rather than switching to a more pelagic diet (Mohan and Walther 2016). However, there is some evidence that, at least under episodic hypoxia, croaker can even, at least temporarily, increase their predation rates by taking advantage of more vulnerable prey (Long and Seitz 2008). There are other pathways by which hypoxia could affect croaker population dynamics that were not included in our model simulations.…”
Section: Discussionmentioning
confidence: 99%
“…Change in one behaviour may influence the outcome of others, for example altered locomotion can affect reproduction and/or food finding behaviour (Boyd et al, 2002). Interspecifically, shifts in locomotion -migration to a new region, shallower burial depths or exposure atop elevated substrates -may change predator-prey relationships (Pihl et al, 1992;Riedel et al, 2008a;Long and Seitz, 2008). Behavioural parameters thus integrate direct and indirect responses across several levels of biological organisation, from individual fitness to community composition, reflecting cascading changes in biodiversity, biogeochemical processes and ecosystem function (e.g.…”
Section: B Riedel Et Al: Effect Of Hypoxia and Anoxia On Invertebramentioning
confidence: 99%